Prevalence and Molecular Epidemiology of Human T-Lymphotropic Virus (HTLV) Infection in People Living With HIV/AIDS in the Pará State, Amazon Region of Brazil - Alencar, Samira Peixoto; Souza, Marlinda de Carvalho; Fonseca, Ricardo Roberto de Souza; Menezes, Cláudia Ribeiro; Azevedo, Vânia Nakauth; Ribeiro, Andre Luis Ribeiro; Lima, Sandra Souza; Laurentino, Rogério Valois; Barbosa, Maria dos Anjos de Abreu Pina; Freitas, Felipe Bonfim; Oliveira-Filho, Aldemir Branco; Machado, Luiz Fernando Almeida (Frontiers in Microbiology, 2020)
The human T-lymphotropic virus (HTLV) is part of the group of retroviruses that share similar routes of transmission to the human immunodeficiency virus (HIV). Coinfection of these viruses can affect the clinical course of both infections, and reports have shown a quicker progression to AIDS and the development of HIV-related opportunistic infections. The current study investigated the demographic characteristics, prevalence, and the subtypes of HTLV among people living with HIV/AIDS (PLWHA) in the State of Pará, Northern Brazil. Blood samples were obtained from patients who were attending a reference unit that provides medical assistance to HIV-infected individuals in the State of Pará, Brazil, during the period of May 2016 to June 2017. Plasma samples were screened by ELISA tests to detect antibodies anti-HTLV-1/2. DNA and viral types were identified by real-time polymerase chain reaction (qPCR). All samples with viral DNA were submitted to nested PCR and nucleotide sequencing. The overall coinfection rate was 1.4% (5/368), and all samples were from subtype HTLV-1a. No cases of HTLV-2 infection were detected. The prevalence of HTLV-1 was higher in females (80%), individuals between 31 and 50 years of age, heterosexual, unmarried, with low monthly income, with secondary educational level or higher, sporadic condom usage, limited number of sexual partners, and no history of sexually transmitted infections. All samples from HTLV-1-infected patients were identified as strains belonging to the subtype 1a (Cosmopolitan), subgroup A (Transcontinental). This study identified that the prevalence of HIV/HTLV coinfection has dropped from 8 to 1.3% in the current investigation. There was a shift of HTLV subtype from a predominance of HTLV-2 infection in the past to an actual exclusively HTLV-1a. There was no significant association between economic, sociodemographic, and behavioral characteristics in HIV/HTLV coinfection.